Conductive thin film, its manufacturing method, and conductive sheet

JP7645117B2Active Publication Date: 2025-03-13ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021057582
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-03-13
Estimated Expiration
2041-03-30

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、導電性に優れ、かつ基材への密着性に優れる薄膜を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645117000002
    Figure 0007645117000002
  • Figure 0007645117000003
    Figure 0007645117000003
  • Figure 0007645117000001
    Figure 0007645117000001
Patent Text Reader

Abstract

To provide a conductive thin film that has low sheet resistance and high adhesion to a substrate.SOLUTION: A conductive thin film is laminated on a substrate and contains a transition metal. The conductive thin film has a density gradient of phosphorus atoms in the thickness direction of the conductive thin film. The density gradient of phosphorus atoms has a maximum value Pm of the phosphorus density in a range from the half of the thickness of the conductive thin film to the substrate.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive thin film, a manufacturing method thereof, and a conductive sheet. [Background technology]

[0002] Conductive thin films composed of transition metals and / or transition metal compounds are used in various electronic devices and are industrially useful. In particular, conductive thin films of transition metals and / or transition metal compounds produced by a method including a precursor coating step are desirable from the viewpoint of large-scale production.

[0003] For example, Patent Document 1 discloses a method for producing a conductive substrate including a conductive thin film in which a dispersion of metal or metal compound particles is printed on a base material and then fired to fuse at least the outermost metal particles, and discloses that the firing is performed by exposing the base material to plasma of a gas containing a reducing gas. In this way, by using plasma treatment for firing, even copper with a relatively high melting point can be sintered, and copper oxide, which is relatively stable in air, can be sintered while being reduced. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5354037 Summary of the Invention [Problem to be solved by the invention]

[0005] Patent Document 1 describes that the oxides remaining without being reduced during the firing process contribute to the adhesion between the conductive thin film formed in this way and the substrate. However, the oxide layer in the conductive thin film has a lower conductivity than metals, and therefore increases the sheet resistance of the thin film. Therefore, it is difficult to achieve both low sheet resistance and adhesion in a conductive thin film, and there has been a demand for the production of a thin film that has adhesion to a substrate even when the oxide layer in the thin film is small.

[0006] The present invention has been made in view of the above problems, and has an object to provide a thin film that has excellent electrical conductivity and excellent adhesion to a substrate. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved by forming a concentration gradient of specific phosphorus atoms in the thickness direction of a conductive thin film, thereby completing the present invention.

[0008] That is, the present invention is as follows. [1] A conductive thin film containing a transition metal is laminated on a substrate, the conductive thin film has a concentration gradient of phosphorus atoms in a thickness direction; The concentration gradient of the phosphorus atoms is such that the maximum atomic concentration P m having Conductive thin film. [2] The average value P of the atomic concentration of the phosphorus in the concentration gradient of the phosphorus atoms a is between 0.1% and 19%. The conductive thin film according to [1]. [3] The average value P a The maximum value P m Ratio (P m / P a ) is 2.0 times or more and 200 times or less, The conductive thin film according to [2]. [4] The maximum value P m is 1.0% or more and 20% or less, The conductive thin film according to any one of [1] to [3]. [5] In the concentration gradient of the phosphorus atoms, the average atomic concentration P of the phosphorus atoms in a range of 30 nm from the side closer to the substrate a30is 0.2% or more and 20% or less, The conductive thin film according to any one of [1] to [4]. [6] The average oxygen atomic concentration O in the thickness direction of the conductive thin film a is 20% or less, The conductive thin film according to any one of [1] to [5]. [7] the thickness of the conductive thin film in a range in which the atomic concentration of oxygen relative to the atomic concentration of the transition metal is 25% or more in the thickness direction of the conductive thin film is 200 nm or less; The conductive thin film according to any one of [1] to [6]. [8] the thickness of the conductive thin film in a range in a thickness direction thereof where the atomic concentration of oxygen is 25% or more is 35% or less of the thickness of the conductive thin film; The conductive thin film according to any one of [1] to [7]. [9] an average atomic concentration Ma of the transition metal in the thickness direction of the conductive thin film is 40% or more and 99% or less; The conductive thin film according to any one of [1] to [8].

[10] The film thickness is 30 nm or more and 1000 μm or less. The conductive thin film according to any one of [1] to [9].

[11] The transition metal comprises a metal of Group 11 of the IUPAC Periodic Table; The conductive thin film according to any one of [1] to

[10] .

[12] The transition metal comprises copper. The conductive thin film according to

[11] .

[13] The maximum value PM of the ratio (P / M) of the atomic concentration P of the phosphorus to the atomic concentration M of the transition metal in the thickness direction of the conductive thin film m is between 1.9% and 100%. The conductive thin film according to any one of [1] to

[12] .

[14] The maximum value PO of the ratio (P / O) of the atomic concentration P of the phosphorus to the atomic concentration O of oxygen in the thickness direction of the conductive thin film m is between 60% and 500%. The conductive thin film according to any one of [1] to

[13] .

[15] A maximum value PMO of a ratio (P / (M+O)) of the atomic concentration P of the phosphorus to the sum of the atomic concentration M of the transition metal and the atomic concentration O of oxygen in the thickness direction of the conductive thin film. m is between 1.9% and 20%. The conductive thin film according to any one of [1] to

[14] .

[16] the conductive thin film includes a particle layer to which particles containing the transition metal are bonded; The conductive thin film according to any one of [1] to

[15] .

[17] the conductive film includes a continuous pattern having openings; The conductive thin film according to any one of [1] to

[16] .

[18] The pattern is a pattern formed by intersecting a plurality of thin lines. The conductive thin film according to

[17] .

[19] The line width of the thin line is 100 nm or more and 1000 μm or less. The conductive thin film according to

[18] .

[20] The pitch of the thin lines is 1.0 μm or more and 1000 μm or less. The conductive thin film according to

[18] or

[19] . 〔twenty one〕 Visible light transmittance is 70% or more and 99% or less. The conductive thin film according to any one of [1] to

[20] . 〔twenty two〕 Sheet resistance is 0.001 Ω cm -2 More than 20Ωcm -2 Below is the The conductive thin film according to any one of [1] to

[21] . 〔twenty three〕 A substrate and the conductive thin film according to any one of [1] to

[22] , Conductive sheet. 〔twenty four〕 The substrate has a plurality of layers. The conductive sheet according to

[23] . 〔twenty five〕 The substrate has a surface layer containing a silicon compound. The conductive sheet according to

[23] or

[24] .

[26] The substrate is a plastic. The conductive sheet according to any one of

[23] to

[25] .

[27] The plastic is polyethylene terephthalate. The conductive sheet according to

[26] .

[28] The conductive thin film according to any one of [1] to

[22] is provided. Touch panel.

[29] The conductive thin film according to any one of [1] to

[22] is provided. display.

[30] The conductive thin film according to any one of [1] to

[22] is provided. Heater.

[31] The conductive thin film according to any one of [1] to

[22] is provided. Electromagnetic wave shielding.

[32] The conductive thin film according to any one of [1] to

[22] is provided. antenna.

[33] The substrate has a phosphorus weight areal density of 6.0 mg m -2 More than 1000mg m -2 A film formation step of forming a precursor thin film, which is and a plasma reaction step of reacting the precursor thin film with plasma for 150 seconds to 60 minutes to obtain a conductive thin film. A method for producing a conductive thin film.

[34] The precursor thin film comprises phosphoric acid and / or a phosphoric acid ester; The method for producing a conductive thin film according to

[33] .

[35] The transition metal weight area density of the precursor thin film is 1.0 g m -2 More than 10g m -2 Below is the The method for producing a conductive thin film according to

[33] or

[34] .

[36] The atmosphere of the plasma reaction process contains a gas that is a molecule containing a hydrogen atom. The method for producing a conductive thin film according to any one of

[33] to

[35] .

[37] The atmosphere of the plasma reaction step includes a rare gas. The method for producing a conductive thin film according to any one of

[33] to

[36] .

[38] In the plasma reaction step, microwave plasma is used. The method for producing a conductive thin film according to any one of

[33] to

[37] . Effect of the Invention

[0009] According to the present invention, it is possible to provide a thin film that has excellent electrical conductivity and excellent adhesion to a substrate. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic cross-sectional view showing an example of a conductive thin film according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic top view illustrating an example of a conductive thin film according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described in detail with reference to the drawings as necessary, but the present invention is not limited to this, and various modifications are possible without departing from the gist of the present invention. In the drawings, the same elements are given the same symbols, and duplicated explanations will be omitted. Furthermore, positional relationships such as up, down, left, and right are based on the positional relationships shown in the drawings, unless otherwise specified. Furthermore, the dimensional ratios of the drawings are not limited to those shown in the drawings.

[0012] 1. Conductive thin film The conductive thin film of the present embodiment is a conductive thin film containing a transition metal that is laminated on a substrate, and has a concentration gradient of phosphorus atoms in the thickness direction of the conductive thin film, and the concentration gradient of phosphorus atoms has a maximum value P m By having such a concentration gradient of phosphorus atoms, the electrical conductivity is further improved, and the adhesion between the conductive thin film and the substrate is further improved.

[0013] The conductive thin film contains transition metal atoms and phosphorus atoms, and may contain oxygen atoms and other atoms as necessary. The transition metal may exist in the form of a metal compound such as an oxide, in addition to the state of a simple metal. The composition of each atom in the conductive thin film will be described in detail below.

[0014] 1.1. Phosphorus Atom Concentration The conductive thin film of this embodiment has a concentration gradient of phosphorus atoms in the thickness direction of the film. The concentration gradient of phosphorus atoms has a maximum phosphorus atomic concentration P m has.

[0015] Fig. 1 shows a schematic cross-sectional view of an example of the conductive thin film of this embodiment. Fig. 1 shows a schematic cross-sectional view of a conductive sheet 100 in which a conductive thin film 10 is disposed on a substrate 20. The conductive thin film 10 shown in Fig. 1 is expressed as a particle layer formed by sintering transition metal particles by plasma, and has pores 11 in its cross section. However, the conductive thin film 10 is not limited to this, and may not have pores 11.

[0016] In this embodiment, "the conductive thin film has a concentration gradient of phosphorus atoms in the thickness direction, and the concentration gradient of the phosphorus atoms is a maximum value P m "Having" means that, as illustrated in the graph of thickness direction and phosphorus atom concentration in Figure 1, the concentration of phosphorus atoms tends to increase closer to the substrate side, and the maximum value Pm of phosphorus atoms is present on the substrate side more than half the film thickness (thickness 0.5T).

[0017] Here, the graph of thickness direction and phosphorus atom concentration shown in Fig. 1 is a plot of the concentration P(t) of phosphorus atoms contained in a cross section of the conductive thin film when the cross section is acquired at a certain thickness position t. Specifically, the graph of thickness direction and phosphorus atom concentration shown in Fig. 1 is a graph in which the concentration of phosphorus atoms contained in the cross section of the conductive thin film is measured and plotted at each thickness position of 0.1T, 0.2T, 0.3T, and T. Note that the measurement accuracy of the plot is an example and can be set to a sufficiently high accuracy.

[0018] Therefore, the maximum value Pm means the maximum value in the graph plotted in this way, and the average value Pa described later means the average value of the phosphorus atom concentration in all thickness directions. In this embodiment, the maximum value is given the subscript "m" (Max), and the average value is given the subscript "a" (average). The same applies to the transition metal atoms, oxygen atoms, and carbon atoms described later.

[0019] It is believed that the adhesion between the conductive thin film and the substrate is improved by having a concentration gradient of phosphorus atoms such that the maximum value of the phosphorus atomic concentration is present on the substrate side. Although the mechanism by which such an improvement in adhesion is observed is not limited to the following, it is believed that the concentration of phosphorus on the substrate side improves the bonding strength between the transition metals present on the substrate side in the conductive thin film and between the substrate and the transition metal, making it more difficult for condensation breakdown and interface peeling to occur. Here, either one of the condensation breakdown and interface peeling may be suppressed, or both may be suppressed. In addition, the improvement in the bonding strength is not limited to the transition metal itself, and the improvement in the bonding strength may occur between the transition metal and the transition metal compound, between the transition metal compounds, or between the transition metal compound and the substrate.

[0020] It is also believed that the conductivity is improved by having a phosphorus atom concentration gradient such that the maximum value of the phosphorus atomic concentration is present on the substrate side. The mechanism by which such an improvement in conductivity is observed is not limited to the following, but it is believed that the amount of oxygen contained in the conductive thin film is reduced by having the phosphorus atomic concentration gradient as described above, the grain boundary resistance of the transition metal is reduced by phosphorus unevenly distributed on the substrate side, or the conductivity is improved by doping phosphorus into a metal compound with low conductivity such as a metal oxide. These reasons may act in combination.

[0021] The above-mentioned concentration gradient of phosphorus atoms can be formed by a film formation step of forming a precursor thin film containing a phosphorus-based compound and a predetermined plasma reaction step. Although the details of the method for producing a conductive thin film having these steps will be described later, it is generally difficult to control the anisotropic movement of phosphorus within the film in the reaction between the precursor thin film and plasma, and it is very surprising that the above-mentioned concentration gradient of phosphorus atoms in which phosphorus is highly concentrated on the substrate side can be obtained by the method described later.

[0022] The maximum atomic concentration of phosphorus, P mis in a thickness range of 1 / 2 the thickness of the film located on the substrate side (0T to 0.5T), preferably in a thickness range of 1 / 4 the thickness of the film located on the substrate side (0T to 0.25T), and more preferably in a thickness range of 1 / 10 the thickness of the film located on the substrate side (0T to 0.1T). m When is within the above range, the sheet resistance of the conductive thin film is further reduced, and the phosphorus concentration distribution tends to be easily adjusted so that the maximum value Pm exists on the substrate side.

[0023] Here, "0T to 0.25T" indicates the range in the thickness direction of the conductive thin film. For example, if the thickness T of the conductive thin film is 100 nm, this means "0×100 nm to 0.25×100 nm" from the substrate side, that is, a thickness range of 0 to 25 nm from the substrate side.

[0024] From the same viewpoint, the maximum atomic concentration of phosphorus, P m In the thickness direction of the conductive thin film, it is preferably in a range of 100 nm from the side closer to the substrate, more preferably in a range of 50 nm from the side closer to the substrate, and even more preferably in a range of 30 nm from the side closer to the substrate.

[0025] Maximum value P m is preferably 0.2 to 20%, more preferably 1.0 to 15%, even more preferably 1.5 to 10%, and still more preferably 2.0 to 5.0%. m By making the maximum value P m By making the concentration of phosphorus 20% or less, it tends to be easier to adjust the phosphorus concentration distribution so that the maximum value Pm exists on the substrate side, and also the concentration of the transition metal in the conductive thin film is relatively increased, so that the sheet resistance of the conductive thin film tends to be further reduced.

[0026] The average atomic concentration of phosphorus in the phosphorus atom concentration gradient, P ais preferably 0.1 to 19%, more preferably 0.1 to 10%, even more preferably 0.1 to 5.0%, and even more preferably 0.1 to 1.0%. a When the thickness is within the above range, the sheet resistance of the conductive thin film tends to be further reduced, and the adhesion between the conductive thin film and the substrate tends to be further improved.

[0027] The degree of uneven distribution of phosphorus in the thickness direction of the conductive thin film is the average value P a Maximum value P for m Ratio (P m / P a ) can be used as an index. m / P a The ratio (P) is preferably 2.0 to 200 times, more preferably 2.5 to 100 times, even more preferably 5.0 to 50 times, and even more preferably 5.0 to 25 times. m / P a When the ratio (P) is 2.0 or more, the degree of uneven distribution of phosphorus toward the substrate increases, so that the sheet resistance of the conductive thin film is further reduced, and the adhesion between the conductive thin film and the substrate tends to be further improved. m / P a ) is 2.0 times or more, the concentration of the transition metal on the opposite side of the conductive thin film from the substrate is relatively increased, and the sheet resistance of the conductive thin film tends to be further reduced. m / P a ) is 200 times or less, so that the ratio (P m / P a ) is easily adjusted to provide a maximum value Pm that satisfies

[0028] In the thickness direction of the conductive thin film, the range of 30 nm from the side closest to the substrate is a portion that contributes to improving the adhesion between the conductive thin film and the substrate, and there is a tendency that interfacial peeling can be suppressed by adjusting the phosphorus atom concentration in this portion. From this perspective, in the concentration gradient of phosphorus atoms, the average phosphorus atomic concentration P a30is preferably 0.2 to 20%, more preferably 1.0 to 15%, even more preferably 1.0 to 10%, and still more preferably 1.5 to 5.0%. a30 When the amount of the adhesive is within the above range, interfacial peeling tends to be further suppressed.

[0029] 1.2.Concentration of transition metal atoms The conductive thin film of the present embodiment contains a transition metal. As described above, in the conductive thin film, the transition metal may be present in the form of a metal compound such as an oxide, in addition to the state of an elemental metal.

[0030] The transition metal atom is not particularly limited as long as it is a metal of Group 3 to Group 11 in the IUPAC periodic table, but it is preferable to include a metal of Group 11, more preferably silver or copper, and even more preferably copper. By using such a transition metal, the conductivity of the conductive thin film tends to be further improved. In addition, since the d orbital of the transition metal that is a metal of Group 3 to Group 11 is not a closed shell, it is thought that the electrons of the d orbital contribute to the bond with phosphorus, and thus the adhesion between the conductive thin film and the substrate is improved. However, the reason for the improvement in adhesion is not limited to the above.

[0031] The type of metal compound containing a transition metal is not particularly limited, but examples thereof include sulfides, selenides, tellurides, nitrides, phosphides, oxides, etc. Among these, oxides are preferable because they are less harmful to the human body and relatively easy to produce.

[0032] In the depth direction of the conductive thin film, the average value Ma of the atomic concentration of the transition metal is preferably 40 to 99%, more preferably 60 to 98%, even more preferably 70 to 97%, and even more preferably 80 to 95%. When the average value Ma is 40% or more, the sheet resistance of the conductive thin film tends to be further reduced. Also, when the average value Ma is 99% or less, the adhesion between the conductive thin film and the substrate tends to be further improved.

[0033] The maximum value PM of the ratio (P / M) of the atomic concentration P of phosphorus to the atomic concentration M of the transition metal in the depth direction of the conductive thin film m is preferably 1.9 to 100%, more preferably 2.0 to 60%, even more preferably 5.0 to 40%, and still more preferably 7.5 to 20%. m By setting the maximum value PM to 1.9%, the adhesion between the conductive thin film and the substrate tends to be improved. m When the ratio is 100% or less, the sheet resistance of the conductive thin film tends to be further reduced.

[0034] The maximum value of the ratio (P / (M+O)) of the atomic concentration of phosphorus P to the sum of the atomic concentration of transition metal M and the atomic concentration of oxygen O in the depth direction of the conductive thin film, PMO m is preferably 1.9 to 20%, more preferably 2.5 to 15%, even more preferably 3.0 to 10%, and still more preferably 3.5 to 7.5%. m By setting the maximum value PMO to 1.9%, the adhesion between the conductive thin film and the substrate tends to be improved. m By making the ratio 20% or less, the sheet resistance of the conductive thin film tends to be further reduced.

[0035] The above ratios (P / M) and (P / (M+O)) are values ​​calculated by measuring the atomic concentration M(t) of the transition metal, the atomic concentration O(t) of oxygen, and the atomic concentration P(t) of phosphorus in the cross section of the conductive thin film at the same thickness position. m and maximum PMO m means the maximum value among the ratio (P / M) and the ratio (P / (M+O)) for each thickness position thus determined.

[0036] 1.3.Oxygen Atomic Concentration The conductive thin film of the present embodiment may contain oxygen atoms. The conductive thin film of the present embodiment may have a concentration gradient of oxygen atoms in the depth direction of the film thickness, or the oxygen atoms may be distributed approximately uniformly.

[0037] The average concentration of oxygen atoms in the depth direction of the conductive thin film, O a is preferably 20% or less, more preferably 1.0 to 15%, even more preferably 2.0 to 12.5%, and even more preferably 3.0 to 7.5%. a By making the average value O 20% or less, the amount of non-conductive transition metal oxide is reduced and the amount of conductive transition metal is relatively increased, so that the sheet resistance of the conductive thin film tends to be further reduced. a By keeping the content of phosphorus at 20% or less, the atomic concentration of phosphorus increases relatively, and this tends to further improve the adhesion between the conductive thin film and the substrate.

[0038] In the conductive thin film, an oxide layer having a high oxygen concentration and a small contribution to conductivity can be expressed by using the ratio of oxygen atoms to the transition metal as an index. Specifically, in this embodiment, the range in which the atomic concentration of oxygen relative to the atomic concentration of the transition metal is 25% or more is defined as the oxide layer. For example, when the transition metal is copper, the value of 25% corresponds to the boundary value at which cuprous oxide and metallic copper exist in a ratio of 1:1. The film thickness of this oxide layer in the conductive thin film is preferably 200 nm or less, more preferably 1.0 to 150 nm, even more preferably 2.0 to 100 nm, even more preferably 3.0 to 50 nm, and even more preferably 3.0 to 20 nm. By the film thickness of the oxide layer being within the above range, the metal layer that relatively contributes to conductivity increases, so that the sheet resistance of the conductive thin film tends to be further reduced. Note that the metal layer is defined as a range in which the atomic concentration of oxygen relative to the atomic concentration of the transition metal is less than 25% as a concept for the oxide layer.

[0039] The thickness of the oxide layer is preferably 35% or less, more preferably 0.5 to 20%, still more preferably 0.5 to 10%, and even more preferably 0.5 to 5.0% of the thickness of the conductive thin film. When the thickness of the oxide layer is within the above range, the sheet resistance of the conductive thin film tends to be further reduced.

[0040] The maximum ratio of the atomic concentration of phosphorus P to the atomic concentration of oxygen O (P / O) in the depth direction of the conductive thin film, PO m is preferably 60 to 500%, more preferably 70 to 400%, even more preferably 80 to 300%, and still more preferably 100 to 200%. m By setting the maximum value PO to 60%, the adhesion between the conductive thin film and the substrate tends to be improved. m When the content is 500% or less, it is within a range that is easy to adjust even when a metal oxide having a relatively excellent stability is used as a precursor.

[0041] 1.4. Carbon atom concentration The conductive thin film of the present embodiment may contain carbon atoms. The conductive thin film of the present embodiment may have a concentration gradient of carbon atoms in the depth direction of the film thickness, or the carbon atoms may be distributed approximately uniformly.

[0042] The average concentration of oxygen atoms in the depth direction of the conductive thin film, C a is preferably 20% or less, more preferably 1.0 to 15%, even more preferably 2.0 to 12.5%, and even more preferably 3.0 to 8.0%. a When the thickness is within the above range, the sheet resistance of the conductive thin film tends to be further reduced, and the adhesion between the conductive thin film and the substrate tends to be further improved.

[0043] 1.5.Method of measuring atomic concentration The concentration of each atom can be determined by calculating the atomic concentration at each thickness position by STEM-EDX analysis of a cross section of the conductive thin film. For example, the average value is the average value when the atomic concentration at each thickness position (atomic concentration at a position 1 nm from the substrate side, atomic concentration at a position 2 nm from the substrate, etc.) is calculated in this manner. The maximum value is the value at which the atomic concentration at each thickness position is maximum. In this embodiment, the concentration of each atom is indicated as element concentration (atom%) unless otherwise specified.

[0044] In the STEM-EDX analysis, a cross section of the conductive thin film is measured, and for example, when the conductive thin film is a thin metal wire pattern described later, the measurement sample is preferably a thin slice including a cross section of the thin metal wire perpendicular to the extension direction of the thin metal wire. In preparing the measurement sample, if necessary, the conductive thin film may be embedded in a support such as an epoxy resin before forming a thin slice.

[0045] The method for forming the thin section is not particularly limited as long as it is a method that can suppress damage to the cross section of the metal thin wire due to the formation and processing of the cross section, but preferably, a processing method using an ion beam (e.g., BIB (Broad Ion Beam) processing method or FIB (Focused Ion Beam) processing method), precision mechanical polishing, ultramicrotome, etc. can be used.

[0046] Next, the cross section of the formed thin metal wire is observed by a scanning transmission electron microscope (STEM) to obtain a STEM image of the cross section of the thin metal wire. At the same time, element mapping of the cross section of the thin metal wire is measured by energy dispersive X-ray analysis (EDX), allowing STEM-EDX analysis to be performed.

[0047] In addition, the fact that the thin film of this embodiment has an atomic concentration distribution in the thickness direction can be evaluated by X-ray photoelectron spectroscopy (XPS) via dry etching as well as STEM-EDX analysis of the cross section of the thin film. The quantitative value of the atomic concentration can be measured by STEM-EDX analysis.

[0048] It is preferable that the formation of a cross section of the thin metal wire and the STEM-EDX analysis described below are carried out in an inert atmosphere of argon or the like or in vacuum in order to prevent oxidation and contamination of the cross section of the thin metal wire.

[0049] 1.6.Film Thickness The thickness of the conductive thin film is preferably 30 nm to 1000 μm, more preferably 50 nm to 100 μm, even more preferably 100 nm to 10 μm, even more preferably 200 to 1000 nm, and even more preferably 300 to 500 nm. When the thickness is 30 nm or more, the sheet resistance of the conductive thin film tends to be further reduced. In addition, the thicker the thickness is, the easier it tends to be to adjust the maximum value Pm to be present on the substrate side in the phosphorus concentration distribution. In addition, when the thickness is 1000 μm or less, the adhesion of the conductive thin film to the substrate tends to be improved. In addition, when the thickness is 1000 μm or less, the conductive thin film tends to be patterned more easily.

[0050] The thickness of the conductive thin film can be determined by a cross-sectional STEM-EDX evaluation of the conductive thin film, which will be described later. More specifically, the region in which the atomic concentration of the transition metal in the conductive thin film is 20% or more is defined as the thickness of the conductive thin film, and the average value of the thickness measured at any three positions can be taken as the thickness of the conductive thin film. Note that the conductive thin film of this embodiment may be a thin film having a uniform thickness, or may be a thin film having unevenness on the surface or having thin portions depending on the position of the conductive thin film.

[0051] The conductive thin film may have no voids in the film or may have voids in the film. Among these, the conductive thin film is preferably one having voids in the film. An example of such a conductive thin film is one containing a particle layer in which particles containing a transition metal are bonded. The particle layer makes the conductive thin film less likely to break even when stress such as bending of the substrate is applied. The conductive thin film composed of such a particle layer can be obtained by a method for producing a thin film using an ink containing particles of a transition metal, which will be described later. The presence of the particle layer can be evaluated by STEM analysis or the like.

[0052] Patterns The conductive thin film may have a continuous pattern with openings, or a solid pattern without openings. The pattern of the conductive thin film can be designed according to the intended use of the electronic device, and may be a regular pattern or an irregular pattern. Here, the opening refers to a portion where the conductive thin film is not present, and light can pass through the opening portion. In addition, the continuous pattern refers to a connection (contact) confirmed by an optical microscope, and such a pattern is electrically connected.

[0053] Among these, the conductive thin film preferably has a continuous pattern having openings. By providing openings in this way, the conductive thin film can be made light-transmitting. The continuous pattern having openings is not particularly limited, but is preferably, for example, a pattern formed by a plurality of crossing thin lines. In this case, the thin lines correspond to the conductive thin film, and the gaps between the thin lines correspond to the openings.

[0054] Specific examples of the pattern formed by a plurality of thin wires are described below, but the pattern in this embodiment is not limited to the following. In the following, the term "thin metal wires" refers to thin conductive thin films, and the term "thin metal wire pattern" refers to a pattern formed by a plurality of thin metal wires.

[0055] Fig. 2 shows a schematic top view of an example of the conductive thin film of this embodiment. Fig. 2 is a top view of a conductive sheet 100 in which a conductive thin film 10 is disposed on a substrate 20, as viewed from the side on which the conductive thin film 10 is formed. In Fig. 2, the conductive thin film 10 is in the form of thin lines, and is shown as a state in which the thin lines cross on a grid. Here, the conductive thin film 10 in the form of thin lines is called a thin metal wire 10'. The cross section of Fig. 1 described above shows the cross section of this thin metal wire 10' taken along the line A-A'.

[0056] 2, the continuous pattern refers to, for example, a configuration in which a plurality of thin metal wires 10' cross each other to form a continuous layer, thereby allowing current to flow between any two points on the conductive thin film 10 spreading in the planar direction. Furthermore, having an opening refers, for example, to having a discontinuous opening 30 between a plurality of thin metal wires 10'. In this embodiment, the conductive continuous layer and openings formed by the thin metal wires 10' are referred to as a thin metal wire pattern 40.

[0057] Here, the line width W of the fine metal wires 10' constituting the fine metal wire pattern 40 refers to the line width of the fine metal wires 10' when the fine metal wires 10' are projected onto the surface of the substrate 20 from the side of the substrate 20 on which the fine metal wire pattern 40 is disposed. The "line width when projected" is defined as the width of the interface between the conductive thin film 10 and the substrate, which is the widest, for example, as shown in Fig. 1. The pitch P is defined as the sum of the line width W and the distance L between the fine metal wires.

[0058] Specific examples of the above-mentioned fine metal wire pattern include a mesh pattern formed by a plurality of fine metal wires crossing each other in a mesh pattern, and a line pattern formed with a plurality of approximately parallel fine metal wires. The fine metal wire pattern may also be a combination of a mesh pattern and a line pattern. The mesh of the mesh pattern may be a square or rectangle, or a polygon such as a rhombus. The fine metal wires constituting the line pattern may be straight or curved. Furthermore, the fine metal wires constituting the mesh pattern may also be curved.

[0059] Line width The line width W is preferably 100 nm to 1000 μm, more preferably 200 nm to 500 μm, even more preferably 300 nm to 100 μm, still more preferably 400 nm to 50 μm, and even more preferably 500 nm to 5.0 μm. The line width W of a thin metal wire having gently sloping side surfaces as shown in FIG. 1 is the width of the thin metal wire disposed perpendicularly to a substrate, and when the substrate in contact with the thin metal wire is a curved surface, it is the perimeter where the cross section of the thin metal wire contacts the substrate.

[0060] By making the line width W of the thin metal wire 100 nm or more, the conductivity of the thin metal wire can be sufficiently ensured, and the sheet resistance tends to be further reduced. In addition, the decrease in conductivity due to oxidation or corrosion of the surface of the thin metal wire can be sufficiently suppressed. Furthermore, for the same aperture ratio, the thinner the line width of the thin metal wire, the more the number of thin metal wires can be increased. This makes the electric field distribution of the conductive sheet more uniform, making it possible to fabricate electronic devices with higher resolution. In addition, even if some of the thin metal wires are broken, the other thin metal wires can compensate for the resulting effect.

[0061] On the other hand, by having the line width W of the thin metal wires be 5.0 μm or less, the visibility of the thin metal wires tends to be reduced, and the transparency of the conductive thin film and the conductive sheet including the same tends to be improved.

[0062] Aspect Ratio The aspect ratio, which is expressed by the thickness T of the thin metal wire relative to the line width W of the thin metal wire, is preferably 0.05 to 1.00, more preferably 0.08 to 0.90, and further preferably 0.10 to 0.80. When the line width W is constant, the larger the aspect ratio, the more the conductivity tends to improve without decreasing the transmittance. In addition, by keeping the aspect ratio at 1.00 or less, a decrease in transmittance due to an excessively thick film thickness tends to be suppressed.

[0063] Pitch The pitch P is preferably 1.0 to 1000 μm, more preferably 5.0 to 500 μm, even more preferably 50 to 250 μm, and even more preferably 100 to 250 μm. When the pitch P is 1.0 μm or more, the transparency of the conductive thin film and the conductive sheet including the same tends to be improved. When the pitch P is 1000 μm or less, the conductivity tends to be improved. When the shape of the thin metal line pattern is a mesh pattern, the pitch of the thin metal line pattern with a line width of 1 μm is set to 200 μm, thereby making it possible to achieve an aperture ratio of 99%.

[0064] 1.8.4.Aperture ratio The aperture ratio of the thin metal line pattern is preferably 60% or more, more preferably 70% or more, even more preferably 80% or more, and particularly preferably 90% or more. When the aperture ratio of the thin metal line pattern is 60% or more, the transmittance of the conductive sheet tends to be further improved.

[0065] The aperture ratio of the thin metal line pattern is preferably less than 100%, more preferably 95% or less, even more preferably 90% or less, still more preferably 80% or less, even more preferably 70% or less, and particularly preferably 60% or less. The aperture ratio of the thin metal line pattern being less than 100% tends to further improve the conductivity of the conductive sheet.

[0066] The appropriate aperture ratio of the thin metal line pattern varies depending on the shape of the thin metal line pattern. In addition, the aperture ratio of the thin metal line pattern can be appropriately combined with the above upper and lower limits depending on the required performance (transmittance and sheet resistance) of the target electronic device.

[0067] The "aperture ratio of the thin metal line pattern" can be calculated for the region on the substrate where the thin metal line pattern is formed by the following formula. The region on the substrate where the thin metal line pattern is formed excludes edges and the like where the thin metal line pattern is not formed. Aperture ratio of thin metal line pattern = (1 - area occupied by thin metal line pattern / area of ​​transparent substrate) x 100

[0068] The line width W, aspect ratio, and pitch P of the thin metal line pattern can be confirmed by observing the cross section of the conductive sheet with an electron microscope or the like. The line width and pitch of the thin metal line pattern can also be observed with a laser microscope or optical microscope. Since the pitch P and the aperture ratio have a relational expression described below, if one is known, the other can be calculated. Methods for adjusting the line width W, aspect ratio, and pitch P of the thin metal line pattern to the desired range include a method of adjusting the grooves of a plate used in the manufacturing method of a conductive sheet described below, and a method of adjusting the average particle size of metal particles in an ink.

[0069] 1.8.5.Visible light transmittance The visible light transmittance of the conductive thin film is preferably 70 to 99%, more preferably 75 to 95%, and further preferably 80 to 90%. The visible light transmittance can be measured by calculating the average transmittance in the visible light range (360 to 830 nm) in accordance with the total light transmittance of JIS K 7361-1:1997. The visible light transmittance of the patterned thin film tends to be improved by reducing the line width of the thin metal line pattern or improving the aperture ratio.

[0070] Sheet Resistance The sheet resistance of the conductive thin film is preferably 0.001 to 20 Ωcm -2 More preferably, it is 0.01 to 17.5 Ωcm -2 and more preferably 0.01 to 15 Ωcm -2 and preferably 0.1 to 10 Ωcm -2 The lower the sheet resistance, the more the electrical conductivity tends to improve.

[0071] The sheet resistance of a conductive sheet tends to decrease by improving the aspect ratio (height) of the thin metal wires. It can also be adjusted by selecting the type of metal material that makes up the thin metal wires.

[0072] 1.8.7.HAZE The haze of the conductive thin film is preferably 0.01 to 5.00%, more preferably 0.01 to 3.00%, and even more preferably 0.01 to 1.00%. When the haze is 5.00% or less, the clouding of the conductive sheet with respect to visible light tends to be further suppressed. The haze in this specification can be measured in accordance with the haze of JIS K 7136:2000.

[0073] 1.9.Applications The conductive thin film of the present embodiment can be applied to various applications. Specific examples include conductive sheets, heaters, electromagnetic wave shields, antennas, etc. In addition, by forming the conductive thin film into a patterned thin film, it can be suitably applied to applications requiring transparency, such as electronic paper, touch panels, and flat panels.

[0074] 2.Conductive sheet The conductive sheet of the present embodiment includes a substrate and the conductive thin film formed on the substrate. Such a conductive sheet becomes a conductive film material, and in particular, when the conductive thin film has the above-mentioned metal thin line pattern and has visible light transparency, it becomes a conductive transparent film material. Such a conductive sheet can provide new value by imparting transparency to heaters, electromagnetic shields, antennas, etc., which have not been required to be transparent in the past, in addition to applications requiring transparency such as touch panels and displays.

[0075] 2.1. Base material The substrate can be appropriately selected according to the application of the conductive sheet, and is not particularly limited. For example, transparent inorganic substrates such as glass, opaque inorganic substrates such as metal plates, transparent or opaque organic substrates such as plastic films can be mentioned. Among these, plastic is preferable from the viewpoint of obtaining a flexible and transparent conductive sheet. In addition, these substrates may have an arbitrary layer on the surface, or may be subjected to an arbitrary surface treatment such as corona treatment.

[0076] The substrate may be in the form of a plate or a film, with the film being preferred from the viewpoint of excellent freedom in shape.

[0077] The plastic is not particularly limited, but examples thereof include transparent organic substrates such as acrylic acid esters, methacrylic acid esters, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyarylate, polyvinyl chloride, polyethylene, polypropylene, polystyrene, nylon, aromatic polyamide, polyether ether ketone, polysulfone, polyethersulfone, polyimide, and polyetherimide.

[0078] Among these, it is preferable to use polyethylene terephthalate (PET) from the viewpoint of high productivity including the cost reduction effect for manufacturing the conductive sheet. Also, it is preferable to use polyimide from the viewpoint of excellent heat resistance of the conductive sheet. Furthermore, it is preferable to use polyethylene terephthalate and / or polyethylene naphthalate from the viewpoint of advantageous adhesion between the thin film and the substrate.

[0079] The substrate of the thin film used in this embodiment may be made of one material or may be a laminate of two or more materials. In addition, when the transparent substrate is a multilayer body in which two or more materials are laminated, the transparent substrate may be a laminate of organic substrates or inorganic substrates, or a laminate of an organic substrate and an inorganic substrate.

[0080] The thickness of the substrate is preferably 5 μm or more and 500 μm or less, and more preferably 10 μm or more and 100 μm or less, from the viewpoint of excellent freedom in shape and / or excellent transparency.

[0081] 2.1.1.Surface layer The substrate may have multiple layers, and may have a surface layer in the area in contact with the conductive thin film. By laminating the surface layer on the substrate, it is possible to prevent etching of the substrate in areas not covered with the thin metal line pattern by plasma or the like when the metal components in the ink are sintered by a baking means such as plasma.

[0082] The components contained in the surface layer are not particularly limited, and examples thereof include silicon compounds (e.g., (poly)silanes, (poly)silazanes, (poly)silthians, (poly)siloxanes, silicon, silicon carbide, silicon oxide, silicon nitride, silicon chloride, silicate salts, zeolites, silicides, etc.), aluminum compounds (e.g., aluminum oxide, etc.), magnesium compounds (e.g., magnesium fluoride), etc. The polysilanes, polysilazanes, polysilthians, and polysiloxanes may have a linear or branched, cyclic, or network-like form. These components may be used alone or in combination of two or more.

[0083] Among these, silicon compounds, aluminum oxide, and magnesium fluoride are preferred, and silicon oxide, silicon nitride, aluminum oxide, and magnesium fluoride are more preferred.By using such components, durability against plasma is improved, and the adhesion between the conductive thin film and the substrate is improved.In addition, by using such components, the transparency and durability of the conductive sheet are improved, and the productivity that contributes to the cost reduction effect for manufacturing the conductive sheet is improved.

[0084] The surface layer can be formed by a vapor phase film formation method such as physical vapor deposition (PVD) or chemical vapor deposition (CVD), or by a method of applying and drying a composition in which the components contained in the surface layer are dispersed in a dispersion medium. This composition may contain a dispersant, a surfactant, a binder, etc., as necessary.

[0085] In addition, when the surface layer is included, silicon may be incorporated into the conductive thin film through a plasma reaction. The silicon atom Si contained in the metal fine wire may exist in the form of a silicon atom or a silicon compound, or in the form in which the silicon atom or the silicon compound is bonded to a metal atom (e.g., Si-M, Si-OM, etc.).

[0086] Thickness The thickness of the surface layer is preferably 0.01 to 500 μm, more preferably 0.05 to 300 μm, and even more preferably 0.10 to 200 μm. When the thickness of the surface layer is 0.01 μm or more, the adhesion between the conductive thin film and the substrate tends to be further improved. Also, when the thickness of the surface layer is 500 μm or less, the flexibility of the substrate can be ensured.

[0087] Volume resistivity The surface layer preferably has an antistatic function to prevent disconnection of the thin metal wire pattern due to static electricity. From the viewpoint of having the antistatic function, the surface layer preferably contains at least one of a conductive inorganic oxide and a conductive organic compound.

[0088] From the viewpoint of antistatic function, the volume resistivity of the surface layer is preferably 100 to 100,000 Ωcm, preferably 1,000 to 10,000 Ωcm, and preferably 2,000 to 8,000 Ωcm. When the volume resistivity of the surface layer is 100,000 Ωcm or less, the antistatic function tends to be further improved. In addition, when the volume resistivity of the surface layer is 100 Ωcm or more, the electrical conductivity between the metal thin line patterns is further reduced, and the surface layer can be suitably used for applications such as touch panels.

[0089] The volume resistivity can be adjusted by the content of conductive inorganic oxides and conductive organic compounds in the surface layer. For example, if the surface layer contains silicon oxide (volume resistivity 1014 Ω·cm or more), which has high plasma resistance, and an organosilane compound, which is a conductive organic compound, the volume resistivity can be reduced by increasing the content of the organosilane compound. On the other hand, although the volume resistivity increases by increasing the content of silicon oxide, it can be made into a thin film because of its high plasma resistance, and the optical properties are not impaired.

[0090] 2.2.Protective layer The conductive sheet of the present embodiment may have a protective layer on the conductive thin film. The protective layer can be formed so as to sandwich the conductive thin film together with the substrate.

[0091] The protective layer is not particularly limited as long as it is transparent and can exhibit good adhesion to the conductive thin film or the substrate. For example, thermosetting resins such as phenolic resin, thermosetting epoxy resin, thermosetting polyimide, melamine resin, urea resin, unsaturated polyester resin, alkyd resin, polyurethane, diallyl phthalate resin, and silicone resin; UV-curable resins such as urethane acrylate, acrylic resin acrylate, epoxy acrylate, silicone acrylate, and UV-curable epoxy resin; and commercially available coating agents can be used.

[0092] 3. Manufacturing method of conductive thin film The method for producing the conductive thin film of this embodiment is to deposit phosphorus on the substrate with a weight area density of 6.0 mg m -2 More than 1000mg m -2 and a plasma reaction step of reacting the precursor thin film with plasma for 150 seconds to 60 minutes to obtain a conductive thin film. If necessary, the method may include a surface layer formation step of forming a surface layer on the substrate before the film formation step.

[0093] 3.1. Surface layer formation process The surface layer forming step is a step of forming the above-mentioned surface layer on the substrate. For example, when a plastic substrate is used, the surface layer can prevent the plastic from being denatured or etched by the plasma reaction.

[0094] A specific example of the surface layer forming method is a method of forming a surface layer by forming a film of a component forming the surface layer on the surface of a transparent substrate using a gas phase film forming method such as physical vapor deposition (PVD) or chemical vapor deposition (CVD). Another specific example of the surface layer forming step is a method of forming a surface layer by applying a composition in which the component forming the surface layer is dispersed in a dispersion medium to the surface of a transparent substrate and drying the composition. In addition, the surface layer forming composition may contain a dispersant, a surfactant, a binder, etc., as necessary.

[0095] In the surface layer forming step, it is preferable to use the above-mentioned silicon compound as a component for forming the surface layer.

[0096] 3.2. Film formation process The film formation process involves applying phosphorus with a weight area density of 6.0 mg m -2 More than 1000mg m -2 The process for forming a precursor thin film is as follows: The weight area density of phosphorus can be adjusted by the amount of phosphorus-based compound contained in the precursor thin film.

[0097] 3.2.1. Precursor thin film The precursor thin film contains a transition metal and / or a transition metal compound and a predetermined amount of phosphorus, and is turned into the conductive thin film of this embodiment by subjecting it to a plasma reaction process described below. As already described, by subjecting such a precursor thin film containing phosphorus to a plasma treatment, the resulting conductive thin film has a phosphorus gradient with a maximum value of the phosphorus atomic concentration on the substrate side, and this phosphorus gradient gives the conductive thin film excellent conductivity and excellent adhesion to the substrate.

[0098] The weight area density of phosphorus in the precursor thin film is 6.0–1000 mg m -2and preferably 8.0 to 500 mg m -2 and more preferably 10 to 100 mg m -2 and more preferably 10 to 50 mg m -2 The weight area density of phosphorus in the precursor thin film is 6.0 mg m -2 When the phosphorus weight area density of the precursor thin film is 1000 mg m or more, the conductivity of the obtained conductive thin film is improved, and the adhesion between the conductive thin film and the substrate is improved. -2 By making the content of the transition metal be equal to or less than this, the electrical conductivity of the obtained conductive thin film is further improved since the content of the transition metal is relatively increased.

[0099] The weight area density of the transition metal in the precursor thin film is preferably 1.0 to 10 g m -2 and more preferably 1.0 to 8.0 g m -2 and more preferably 1.0 to 6.0 g m -2 When the weight area density of the transition metal in the precursor thin film is within the above range, the electrical conductivity of the obtained conductive thin film tends to be further improved, and the adhesion between the conductive thin film and the substrate tends to be further improved.

[0100] In this embodiment, the weight density of phosphorus or transition metal in the precursor thin film refers to the weight density of phosphorus or transition metal in the region where the precursor thin film is present, and when the pattern has openings, the openings are not included in the calculation of the weight area density of phosphorus or transition metal.

[0101] The phosphorus-based compound contained in the precursor thin film is not particularly limited, and may be, for example, phosphoric acid and / or a phosphoric acid ester. By using such a phosphorus-based compound, a phosphorus gradient having a maximum value of the phosphorus atomic concentration on the substrate side tends to be more easily formed in the plasma reaction process described later.

[0102] Such a precursor thin film can be formed by various methods such as a dry method using a vacuum device, etc., a wet method using an ink, etc. Among these, a method of forming a precursor thin film by printing an ink on a substrate is preferred from the viewpoints of suitability for large-scale production and ease of adjusting the amount of phosphorus to be contained in the precursor thin film.

[0103] The printing method that can be used is not particularly limited, and examples thereof include letterpress printing, gravure printing, bar coating, spray coating, spin coating, reverse transfer printing, etc. Among these, from the viewpoint of being able to print a relatively precise pattern, formation of the precursor thin film by a plate printing method is preferred.

[0104] Examples of plate-based printing methods include a step of coating the surface of a transfer medium with ink, a step of contacting the ink-coated transfer medium surface with the convex surface of a letterpress plate to transfer a portion of the ink on the transfer medium surface to the convex surface of the letterpress plate, and a step of contacting the transfer medium surface after some of the ink has been transferred with the surface of a substrate to transfer the ink remaining on the transfer medium surface to the surface of the substrate.

[0105] For example, in such a printing method, various shapes of the precursor thin film, such as thickness, width, pitch, etc., and the concentration of each atom contained in the precursor thin film can be controlled by adjusting the printing conditions and ink.

[0106] Ink The ink used in the above printing method contains a metal component, a solvent, and a phosphorus component, and may contain a surfactant, a dispersant, a reducing agent, etc., as necessary.

[0107] 3.2.2.1. Metal particles The metal component may be contained in the ink as metal particles or as a metal complex. Among these, it is preferable that the metal component is contained in the ink as metal particles. As the metal particles, as long as they contain the above-mentioned transition metal atoms, they may be metal oxides such as copper oxide or other metal compounds, or core / shell particles in which the core part is copper and the shell part is copper oxide. Among these, metal oxides such as copper oxide are preferable from the viewpoint of handling.

[0108] The average primary particle size of the metal particles is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 30 nm or less. The lower limit of the average primary particle size of the metal particles is not particularly limited, but may be 1 nm or more. From the viewpoint of making the line width W of the obtained thin metal wires thinner, the average primary particle size of the metal particles is preferably 100 nm or less.

[0109] The average secondary particle size of the metal particles is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 30 nm or less. From the viewpoint of excellent coatability during thin film formation, it is preferable that each particle is monodispersed and the average secondary particle size is close to the average primary particle size.

[0110] In this embodiment, the "average primary particle size" refers to the particle size of each individual metal particle (so-called primary particle), and is distinguished from the average secondary particle size, which is the particle size of an aggregate (so-called secondary particle) formed by multiple metal particles gathering together.

[0111] 3.2.2.2. Phosphorus Content The phosphorus component is not particularly limited, but examples thereof include black phosphorus, red phosphorus, phosphoric acid, and phosphoric acid esters. Among these, phosphoric acid and / or phosphoric acid esters are preferred. By using such phosphorus-based compounds, a phosphorus gradient having a maximum phosphorus atomic concentration on the substrate side tends to be more easily formed in the plasma reaction process described below. The phosphoric acid and / or phosphoric acid ester includes polymers and low molecules having phosphoric acid groups and / or phosphoric acid ester groups, phosphate anions, phosphate ester anions, salts containing phosphate anions, and salts containing phosphate ester anions.

[0112] In addition, for example, a surfactant, a pH adjuster, a viscosity adjuster, a drying speed adjuster, a dispersant for metal particles, a stabilizer, etc., which contain phosphorus atoms, may be used as the phosphorus component. Examples of such phosphorus components include dispersants having a phosphate ester group.

[0113] Surfactants The surfactant is not particularly limited, but examples thereof include fluorine-based surfactants and silicone-based surfactants. By using such surfactants, the coatability of the ink on the transfer medium (blanket) and the smoothness of the coated ink are improved, and a more uniform coating film tends to be obtained. It is preferable that the surfactant is configured to be capable of dispersing metal components and to be unlikely to remain after baking.

[0114] Solvent The ink solvent is preferably an organic solvent from the viewpoints of excellent storage stability and small light loss. From the above viewpoints, the organic solvent is preferably an alcohol. From the above viewpoints, the number of carbon atoms in the organic solvent is preferably 1 to 7, more preferably 2 or more, more preferably 5 or less, or 4 or less, and most preferably 2.Examples of the solvent include water, propylene glycol monomethyl ether acetate, 3-methoxy-3-methyl-butyl acetate, ethoxyethyl propionate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol tertiary butyl ether, dipropylene glycol monomethyl ether, ethylene glycol butyl ether, ethylene glycol ethyl ether, ethylene glycol methyl ether, ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 2-pentanediol, 2-methylpentane-2,4-diol, 2,5-hexanediol, 2,4-heptanediol, 2-ethylhexane-1,3-diol, diethylene glycol, hexanediol, octanediol, triethylene glycol, tri-1,2-propylene glycol, glycerol, ethylene glycol monohexyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl acetate, diethylene glycol, monoethyl ether acetate, methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, 2-butanol, t-butanol, n-pentanol, i-pentanol, 2-methylbutanol, 2-pentanol, t-pentanol, 3-methoxybutanol, n-hexanol, 2-methylpentanol, 1-hexanol, 2-hexanol, 2-ethylbutanol, 1-heptanol, 2-heptanol, 3-heptanol, n-octanol, 2-ethylhexanol, 2-octanol, n-nonyl Examples of the alcohol include alcohol, 2,6-dimethyl-4-heptanol, n-decanol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, benzyl alcohol, and diacetone alcohol. From the viewpoints of excellent storage stability and low light loss, methanol, ethanol, propanol, butanol, pentanol, hexanol, heptanol, and isomers thereof are more preferable, ethanol, propanol, butanol, and isomers thereof are even more preferable, and ethanol is the most preferable.

[0115] Dispersants The dispersant is not particularly limited, but examples thereof include dispersants that non-covalently bond or interact with metal components, and dispersants that covalently bond with metal components. Examples of functional groups that non-covalently bond or interact with metal components include dispersants having a phosphate group. By using such dispersants, the dispersibility of metal components tends to be further improved.

[0116] 3.3.Plasma reaction process The plasma reaction process is a process in which the precursor thin film formed as described above is reacted with plasma for 150 seconds to 60 minutes to obtain a conductive thin film. As a result, the precursor thin film is baked, and the metal particles in the ink are sintered to form a particle layer (conductive thin film), and the phosphorus contained in the precursor thin film migrates to the substrate side, forming a predetermined concentration gradient. As a result, a conductive thin film with excellent conductivity and adhesion to the substrate can be obtained. In addition, by making the atmosphere during the plasma reaction a reducing type, the oxygen concentration contained in the conductive thin film can also be adjusted.

[0117] Plasma can be generated by various methods. Among them, microwave plasma and high frequency plasma are preferable because they are relatively easy to control, and microwave plasma is more preferable from the viewpoint of reducing contamination caused by electrodes for generating plasma in the apparatus.

[0118] The microwave output of the microwave plasma is preferably 0.5 to 10 kW, more preferably 1.0 to 5.0 kW. By using a microwave output of 0.5 kW or more, the adhesion between the obtained conductive thin film and the substrate is improved, and the plasma reaction time can be shortened. In addition, by using a microwave output of 10 kW or less, etching or modification of the substrate by the plasma tends to be suppressed.

[0119] The treatment time of the plasma reaction is 150 seconds to 60 minutes, preferably 180 to 600 seconds, and more preferably 240 to 360 seconds. By setting the treatment time to 150 seconds or more, phosphorus tends to be unevenly distributed on the substrate side in the conductive thin film, and the maximum value of the phosphorus concentration unevenly distributed on the substrate side becomes larger, which tends to further improve the adhesion between the conductive thin film and the substrate. In addition, by setting the treatment time to 60 minutes or less, the productivity of the conductive thin film tends to further improve.

[0120] The atmosphere of the plasma reaction preferably contains a gas containing molecules containing hydrogen atoms or a rare gas. In particular, a gas containing hydrogen molecules and / or water molecules is more preferable, and a gas containing hydrogen molecules is even more preferable. The gas containing molecules containing hydrogen atoms is not particularly limited, but is preferably, for example, a gas containing hydrogen molecules. The gas containing molecules containing hydrogen atoms may be one or more types of molecules. By using such a gas containing molecules containing hydrogen atoms, the conductivity of the conductive thin film to be manufactured tends to be further improved.

[0121] The rare gas is not particularly limited, but examples thereof include helium, argon, xenon, and krypton. Among these, helium or argon, which have relatively small molecular weights, are preferred, and helium is most preferred, from the viewpoint of reducing sample etching by these plasmas. By using such a rare gas, the plasma reaction can be more easily controlled.

[0122] The gas of molecules containing hydrogen atoms and the rare gas may be mixed and used, or other gases may be further mixed therewith. From the viewpoint of having reducing properties during the plasma reaction and being able to relatively easily control the reduction reaction, it is preferable to use both the gas of molecules containing hydrogen atoms and the rare gas. Specifically, it is preferable to use a gas that contains both hydrogen molecules and helium.

[0123] The pressure of the plasma reaction may be under pressure, reduced pressure, or atmospheric pressure. Among these, reduced pressure is preferable from the viewpoint of lengthening the mean free path of the plasma. Specifically, the pressure is preferably 0.1 to 1000 Pa, more preferably 1.0 to 500 Pa, and further preferably 10 to 300 Pa. When the pressure is 0.1 Pa or more, the mean free path of the plasma tends to be longer. Furthermore, when the pressure is 1000 Pa, it is possible to use a larger amount of gas or rare gas, which is a molecule containing hydrogen atoms.

[0124] 4. Touch Panel The touch panel of the present embodiment is not particularly limited as long as it includes the conductive thin film. For example, in a capacitive touch panel, two conductive sheets (conductive thin films) are present on the front and back surfaces of an insulator, and the two conductive sheets face each other so that, for example, the line patterns of thin metal wires cross. The conductive sheets are connected to an extraction electrode, and the extraction electrode 32 connects the thin metal wires to a controller (such as a CPU) for switching the current flow to the thin metal wires.

[0125] The touch panel of the present embodiment is not limited to a capacitive type, and may be a resistive film type, a projected capacitive type, a surface capacitive type, or the like.

[0126] 5. Display The display of the present embodiment is not particularly limited as long as it includes the conductive thin film. For example, an organic electroluminescence (EL) display has a structure in which an organic EL film is sandwiched between electrodes, and the conductive thin film can be used as one of the electrodes. Also, a liquid crystal display has a structure in which a liquid crystal layer is sandwiched between electrodes, and the conductive thin film can be used as one of the electrodes.

[0127] 6. Heater The heater of the present embodiment is not particularly limited as long as it is equipped with the conductive thin film. For example, an electric heater has an electric heating part that generates Joule heat when electricity is supplied, and a power supply device that supplies power to the electric heating part, and a conductive sheet (conductive thin film) can be used as the electric heating part. If the conductive sheet (conductive thin film) is configured to be transparent, it becomes a transparent heater, and if the conductive sheet is designed to have a high resistance, it becomes a heater with a high heat generation amount.

[0128] For example, the use of the transparent heater is not particularly limited, but examples thereof include anti-fogging or anti-freezing heaters for LED lighting fixtures used in automobile headlamps, taillamps, etc., and anti-fogging or anti-freezing heaters for outdoor LED lighting fixtures used in street lamps, etc.

[0129] 7.Electromagnetic Shielding The electromagnetic wave shield of the present embodiment is not particularly limited as long as it includes the conductive thin film. For example, the electromagnetic wave shield has a shielding material that reflects or absorbs incident electromagnetic waves, and the conductive thin film can be used as the shielding material.

[0130] 8. Antenna The antenna of this embodiment is not particularly limited as long as it is equipped with the conductive thin film. For example, in an RF tag, a semiconductor element and an antenna connected thereto are provided, enabling transmission and reception of a specific frequency, and a conductive sheet (conductive thin film) can be used as the antenna. If the conductive sheet (conductive thin film) is made transparent, it becomes a transparent antenna. EXAMPLES

[0131] Hereinafter, the present embodiment will be described in more detail with reference to specific examples and comparative examples. However, the present embodiment is not limited in any way by these examples and comparative examples as long as the gist of the present embodiment is not exceeded.

[0132] (Evaluation of element concentration distribution in cross section of thin metal wire) The obtained substrate with the conductive thin film was cut with a razor, embedded in a vapor-deposited carbon layer, and thin slices with a thickness of about 100 nm were formed with a focused ion beam. The obtained thin slices were used as measurement samples, and irradiated with an electron beam under the following conditions to prepare evaluation samples, and STEM-EDX analysis was performed. This analysis obtained the concentration distributions of transition metals, phosphorus, oxygen, and carbon in the thickness direction of the conductive thin film every 2.8 nm or 3.4 nm. In addition, the parameters listed in Table 1 were calculated based on the obtained concentration distributions. [Equipment conditions] STEM: Hitachi High-Technologies Corporation, scanning transmission electron microscope HD-2300A EDX: EDAX Energy Dispersive X-ray Analysis System Octane T Plus (Software: GENESIS) Accelerating voltage: 200kV Measurement magnification: 100,000x Mapping elements: Cu, O, P, Si, C

[0133] (Position of maximum phosphorus concentration in thin film) The position of the maximum phosphorus atomic concentration was evaluated based on the distribution of phosphorus atomic concentration obtained by evaluating the element concentration distribution in the cross section of the metal thin wire. The maximum phosphorus atomic concentration in the conductive thin film was defined as "near the substrate" when it was within 10% of the thickness direction from the side closest to the substrate, as "near the substrate," when it was within a range of more than 1 / 4 and within 1 / 2, as "on the substrate side," when it was within a range of more than 1 / 2 and within 3 / 4, as "on the thin film surface side," and when it was within a range of more than 3 / 4 to the thin film surface, as "near the thin film surface."

[0134] (Average P atom concentration at the thin film-substrate interface) The average phosphorus atomic concentration density of the conductive thin film was calculated for a region from the side closest to the substrate interface up to 30 nm in thickness, using the distribution of phosphorus atomic concentration obtained by evaluating the element concentration distribution of the cross section of the metal wire.

[0135] (Oxide layer thickness) Based on the distribution of oxygen atomic concentration obtained by evaluating the element concentration distribution in the cross section of the metal thin wire, the film thickness in the range where the oxygen atomic concentration relative to the transition metal atomic concentration is 25% or more was specified as the film thickness of the oxide layer. In addition, the ratio of the film thickness of the oxide layer to the film thickness of the conductive thin film was calculated.

[0136] (Thin film morphology evaluation) The thickness of the conductive thin film and the fact that the conductive thin film is a particle layer formed by sintering metal particles together were determined from the STEM image of the cross-sectional STEM-EDX analysis described above. Furthermore, the pattern shape, line width, and pitch of the conductive thin film were evaluated using a laser microscope (OLYMPUS, OLS-4500).

[0137] (Sheet resistance evaluation) The sheet resistance was measured using a non-contact resistance meter (NC-700) using eddy current manufactured by NAPSON.

[0138] (Visible light transmittance) The visible light transmittance was calculated by the following method. (Visible light transmittance) = (opening ratio of thin line pattern) × (visible light transmittance of substrate)

[0139] (Adhesion) The adhesion of the conductive thin film to the substrate was evaluated by the following tape peeling test and laser microscope observation. Before the tape peeling test, the sample was observed with a laser microscope (OLYMPUS, OLS-4500), and the obtained image was recorded. The adhesive surface of an adhesive tape (3M No. 610) was brought into contact with the conductive thin film, and the tape was fixed by rolling a 2N (Newton) roller twice from above the tape. The fixed tape was peeled off at a speed of 100 mm / min using a 90° peel tester (Shimadzu Corporation, EZ-S), and a tape peeling test was performed. The substrate surface after this tape peeling was observed with a laser microscope in the same manner as that measured before the tape peeling test, and the obtained image was recorded. The obtained images before and after the tape peeling test were subjected to a binarization process to determine the boundary by Otsu's method, and then the area of ​​the metal thin line part was compared, and the area ratio of the metal thin line part lost by the tape peeling test was obtained to obtain the peeled area ratio of the metal thin line by the tape peeling test. The smaller this peeled area ratio, the better the adhesion of the thin film to the substrate.

[0140] <Example 1> (Preparation of Transparent Substrate) A surface layer-forming composition containing silicon oxide nanoparticles and a conductive organosilane compound was applied onto a transparent substrate made of polyethylene terephthalate (PET), and then dried to form a surface layer containing silicon oxide with an antistatic function, a thickness of 150 nm, and a volume resistivity of 5000 Ωcm, to obtain a substrate. This substrate has a surface layer laminated on the substrate, PET.

[0141] (Ink Preparation) 20 parts by mass of cuprous oxide nanoparticles with a primary particle size of 21 nm, 4 parts by mass of a dispersant which is a polymer having a phosphate ester group (manufactured by Big-Chemie, product name: Disperbyk-145), 1 part by mass of a surfactant (manufactured by Seimi Chemical, product name: S-611), and 75 parts by mass of ethanol were mixed to prepare an ink containing 20% ​​by mass of cuprous oxide nanoparticles.

[0142] (Preparation of precursor thin film) First, ink was applied to the surface of the transfer medium, and then the ink-coated surface of the transfer medium was brought into contact with a plate with grooves of a fine metal line pattern, and some of the ink on the surface of the transfer medium was transferred to the raised surface of the plate. After that, the surface of the transfer medium coated with the remaining ink was brought into contact with a substrate, and the ink in the form of the fine metal line pattern was transferred onto the substrate. Through this process, a precursor thin film was produced. The film thickness of this precursor thin film was 680 nm, and the deposition concentration of phosphorus was 10 mg m -2 , the copper deposition concentration was 1.6 g m -2 The precursor phosphorus species were phosphoric acid and phosphate ester. The results are shown in Table 1.

[0143] (Plasma reaction process) The precursor thin film produced in the above process was subjected to a plasma reaction. Specifically, plasma was generated by microwaves generated at an output of 1.5 kW in an atmosphere containing 3% hydrogen by volume and 97% helium by volume under reduced pressure, and the precursor thin film was reacted with this plasma for 5 minutes.

[0144] The thin film of Example 1 was subjected to atomic concentration analysis of the thin film cross section, morphology evaluation, sheet resistance measurement, transmittance estimation, and adhesion evaluation. These results are shown in Table 1.

[0145] <Example 2> The precursor thin film obtained in the same manner as in Example 1 was subjected to a plasma reaction step, and the procedure was the same as in Example 1, except that the plasma reaction treatment time was 3 minutes. The results are shown in Table 1.

[0146] <Comparative Example 1> The precursor thin film obtained in the same manner as in Example 1 was subjected to a plasma reaction process, and the procedure was the same as in Example 1, except that the plasma reaction treatment time was 1 minute. The results are shown in Table 1.

[0147] <Comparative Example 2> The precursor thin film obtained in the same manner as in Example 1 was subjected to a plasma reaction step, and the procedure was the same as in Example 1, except that the plasma reaction treatment time was set to 2 minutes. The results are shown in Table 1.

[0148] Examples 1 and 2 had a distribution in the atomic concentration of phosphorus and had a maximum value of phosphorus on the side closer to the substrate than half of the thin film thickness, and thus satisfied this embodiment. On the other hand, Comparative Examples 1 and 2 had a maximum value of phosphorus on the side closer to the thin film surface than half of the thin film thickness, and thus did not satisfy this embodiment. Furthermore, Examples 1 and 2 had a small peeled area ratio of 4% or less after the adhesion test, whereas Comparative Examples 1 and 2 had a large peeled area ratio of 14% or more. Thus, by satisfying this embodiment, it was shown that the thin film has excellent adhesion to the substrate.

[0149] In addition, Examples 1 and 2 showed lower sheet resistance than Comparative Examples 1 and 2. This shows that by satisfying the present embodiment, a thin film with low sheet resistance and excellent conductivity can be obtained.

[0150] The weight area density of phosphorus is 6 mg m -2 More than 1000mg m -2 The conductive thin films of Examples 1 and 2, which satisfy the present embodiment, were obtained by performing plasma treatment for 150 seconds to 60 minutes on the precursor thin film described below. It was shown that the conductive thin film of the present embodiment can be preferably obtained by including this step in the manufacturing method.

[0151] Regarding the amount of oxygen in the thin film, the average value of the oxygen atomic concentration in the thin film, the oxide layer thickness, and the oxide layer thickness ratio were smaller in Examples 1 and 2 than in Comparative Examples 1 and 2. However, surprisingly, Examples 1 and 2 had better adhesion than Comparative Examples 1 and 2. This is presumably due to the effect of phosphorus being unevenly distributed on the substrate side.

[0152] [Table 1] [Industrial Applicability]

[0153] The conductive thin film of the present invention has industrial applicability as an element constituting a transparent or non-transparent conductive sheet. [Explanation of symbols]

[0154] 10...conductive thin film, 10'...metallic thin wire, 11...hole, 20...substrate, 30...opening, 40...metallic thin wire pattern, 100...conductive sheet

Claims

1. A conductive thin film containing a transition metal is laminated on a substrate, the conductive thin film has a concentration gradient of phosphorus atoms in a thickness direction; The concentration gradient of the phosphorus atoms is such that the maximum atomic concentration P m having Conductive thin film.

2. The average value P of the atomic concentration of phosphorus in the concentration gradient of the phosphorus atoms a is 0.1% or more and 19% or less, The conductive thin film according to claim 1 .

3. The average value P a The maximum value P m The ratio (P m / P a ) is 2.0 times or more and 200 times or less; The conductive thin film according to claim 2 .

4. The maximum value P m is 1.0% or more and 20% or less, The conductive thin film according to any one of claims 1 to 3.

5. In the concentration gradient of the phosphorus atoms, the average atomic concentration P of the phosphorus atoms in a range of 30 nm from the side closer to the substrate a30 is 0.2% or more and 20% or less, The conductive thin film according to any one of claims 1 to 4.

6. The average oxygen atomic concentration O in the thickness direction of the conductive thin film a is 20% or less, The conductive thin film according to any one of claims 1 to 5.

7. a thickness of the conductive thin film in a range in which the atomic concentration of oxygen relative to the atomic concentration of the transition metal is 25% or more in a thickness direction of the conductive thin film is 200 nm or less; The conductive thin film according to any one of claims 1 to 6.

8. a thickness of the conductive thin film in a range in a thickness direction thereof where the atomic concentration of oxygen is 25% or more is 35% or less of the thickness of the conductive thin film; The conductive thin film according to any one of claims 1 to 7.

9. an average atomic concentration Ma of the transition metal in a thickness direction of the conductive thin film is 40% or more and 99% or less; The conductive thin film according to any one of claims 1 to 8.

10. The film thickness is 30 nm or more and 1000 μm or less. The conductive thin film according to any one of claims 1 to 9.

11. The transition metal comprises a metal of Group 11 of the IUPAC Periodic Table; The conductive thin film according to any one of claims 1 to 10.

12. The transition metal comprises copper. The conductive thin film according to claim 11.

13. The maximum value PM of the ratio (P / M) of the atomic concentration P of the phosphorus to the atomic concentration M of the transition metal in the thickness direction of the conductive thin film. m is 1.9% or more and 100% or less, The conductive thin film according to any one of claims 1 to 12.

14. The maximum value PO of the ratio (P / O) of the atomic concentration P of the phosphorus to the atomic concentration O of oxygen in the thickness direction of the conductive thin film m is 60% or more and 500% or less, The conductive thin film according to any one of claims 1 to 13.

15. a maximum value PMO of a ratio (P / (M+O)) of the atomic concentration P of the phosphorus to the sum of the atomic concentration M of the transition metal and the atomic concentration O of oxygen in the thickness direction of the conductive thin film; m is 1.9% or more and 20% or less, The conductive thin film according to any one of claims 1 to 14.

16. the conductive thin film includes a particle layer to which particles containing the transition metal are bonded; The conductive thin film according to any one of claims 1 to 15.

17. the conductive film includes a continuous pattern having openings; The conductive thin film according to any one of claims 1 to 16.

18. The pattern is a pattern formed by intersecting a plurality of thin lines. The conductive thin film according to claim 17.

19. The line width of the thin line is 100 nm or more and 1000 μm or less. The conductive thin film according to claim 18.

20. The pitch of the thin lines is 1.0 μm or more and 1000 μm or less.

20. The conductive thin film according to claim 18 or 19.

21. The visible light transmittance is 70% or more and 99% or less. The conductive thin film according to any one of claims 1 to 20.

22. Sheet resistance is 0.001 Ω cm -2 20Ωcm or more -2 Below is the The conductive thin film according to any one of claims 1 to 21.

23. A substrate and the conductive thin film according to any one of claims 1 to 22. Conductive sheet.

24. The substrate has a plurality of layers. The conductive sheet according to claim 23.

25. The substrate has a surface layer containing a silicon compound. The conductive sheet according to claim 23 or 24.

26. The substrate is a plastic. The conductive sheet according to any one of claims 23 to 25.

27. The plastic is polyethylene terephthalate. The conductive sheet according to claim 26.

28. The conductive thin film according to any one of claims 1 to 22 is provided. Touch panel.

29. The conductive thin film according to any one of claims 1 to 22 is provided. display.

30. The conductive thin film according to any one of claims 1 to 22 is provided. Heater.

31. The conductive thin film according to any one of claims 1 to 22 is provided. Electromagnetic wave shielding.

32. The conductive thin film according to any one of claims 1 to 22 is provided. antenna.

33. The substrate has a phosphorus weight areal density of 6.0 mg m -2 1000mg・m or more -2 A film formation step of forming a precursor thin film, which is as follows: and a plasma reaction step of reacting the precursor thin film with plasma for 150 seconds to 60 minutes to obtain a conductive thin film. A method for producing a conductive thin film.

34. The precursor thin film comprises phosphoric acid and / or a phosphoric acid ester; The method for producing a conductive thin film according to claim 33.

35. The weight area density of the transition metal in the precursor thin film is 1.0 g m -2 10g・m or more -2 Below is the The method for producing a conductive thin film according to claim 33 or 34.

36. The atmosphere of the plasma reaction process contains a gas that is a molecule containing a hydrogen atom. The method for producing a conductive thin film according to any one of claims 33 to 35.

37. The atmosphere of the plasma reaction step includes a rare gas. The method for producing a conductive thin film according to any one of claims 33 to 36.

38. In the plasma reaction step, microwave plasma is used. The method for producing a conductive thin film according to any one of claims 33 to 37.

Citation Information

Patent Citations

  • Heat printing head

    JP1978054037A

  • Dispersion

    JP2020019963A

  • Conductive pattern production method and plasma processor

    JP2020145194A

  • Metal nanoparticle containing complex, fluid dispersion thereof and production methods for metal nanoparticle containing complex and fluid dispersion thereof

    WO2011048876A1

  • Dispersant, metal particle dispersion for conductive substrate, and production method for conductive substrate

    WO2014061750A1